Atomically thin mesoporous NiCo2O4 grown on holey graphene for enhanced pseudocapacitive energy storage. Issue 27 (18th May 2020) - Yuan, Ding; Dou, Yuhai; Xu, Li; Yu, Linping; Cheng, Ningyan; Xia, Qingbing; Hencz, Luke; Ma, Jianmin; Dou, Shi Xue; Zhang, Shanqing
Abstract : Pseudocapacitive charge storage at the surface/interface of atomically thin mesoporous heterostructures is promising for achieving both high energy density and high power density in lithium-ion batteries (LIBs). Abstract : Pseudocapacitive energy storage via Li + storage at the surface/interface of the electrode is promising for achieving both high energy density and high power density in lithium-ion batteries (LIBs). Thus, we created holey graphene (HG) via an etching method, and then in situ grew atomically thin mesoporous NiCo2 O4 nanosheets on the HG surface, resulting in a NiCo2 O4 –HG heterostructure. Since both NiCo2 O4 and HG possess atomic thickness and porous structures, the as-prepared nanocomposite enables efficient electrolyte diffusion and mass transfer, providing abundant accessible surface atoms for enhanced redox pseudocapacitance. Moreover, the strong coupling effect between NiCo2 O4 and graphene produces an ultra-large interfacial area and enhanced electrical conductivity, and subsequently promotes the intercalation pseudocapacitance. Consequently, the NiCo2 O4 @HG exhibits a high specific capacity of 1103.4 mA h g −1 at 0.2C, ∼88.9% contribution from pseudocapacitance at 1 mV s −1, excellent rate capability, and ultra-long life up to 450 cycles with 931.2 mA h g −1 retention, significantly outperforming previously reported electrodes. This work suggests that the maximum exposure and utilization of the surface/interfacial active sites is vital for the construction of high-performance pseudocapacitive energy storage devices.